Clinical characteristics of newly diagnosed primary, pigmentary and pseudoexfoliative open-angle glaucoma in the Collaborative Initial Glaucoma Treatment Study. Issue 9 (6th July 2012) - Musch, David C; Shimizu, Takayuki; Niziol, Leslie M; Gillespie, Brenda W; Cashwell, L Frank; Lichter, Paul R
Abstract : Background/aims: Three types of open-angle glaucoma (OAG)—primary, pigmentary and pseudoexfoliative—are frequently encountered. The aim of this study was to compare demographic, ocular and systemic medical information collected on people with these three OAG types at diagnosis, and determine if the OAG type affected the prognosis. Methods: Information on 607 participants of the Collaborative Initial Glaucoma Treatment Study was accessed. Descriptive statistics characterised their demographic, ocular and medical status at diagnosis. Comparisons were made using analysis of variance and χ 2 or Fisher's exact tests. Multinomial, mixed and logistic regression analyses were also performed. Results: Relative to people with primary OAG, those with pigmentary OAG were younger, more likely to be white, less likely to have a family history of glaucoma, and were more myopic. Those with pseudoexfoliative OAG were older, more likely to be white, more likely to be women, less likely to have bilateral disease, and presented with higher intraocular pressure (IOP) and better visual acuity. The type of glaucoma was not associated with IOP or visual field progression during follow-up. Conclusion: Characteristics of newly diagnosed enrollees differed by the type of OAG. While some of these differences relate to the pathogenesis of OAG type, other differences are noteworthy for further evaluation within population-based samples of subjects with newly diagnosed OAG.